-5(x+1)+11=36

Simple and best practice solution for -5(x+1)+11=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x+1)+11=36 equation:


Simplifying
-5(x + 1) + 11 = 36

Reorder the terms:
-5(1 + x) + 11 = 36
(1 * -5 + x * -5) + 11 = 36
(-5 + -5x) + 11 = 36

Reorder the terms:
-5 + 11 + -5x = 36

Combine like terms: -5 + 11 = 6
6 + -5x = 36

Solving
6 + -5x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -5x = 36 + -6

Combine like terms: 6 + -6 = 0
0 + -5x = 36 + -6
-5x = 36 + -6

Combine like terms: 36 + -6 = 30
-5x = 30

Divide each side by '-5'.
x = -6

Simplifying
x = -6

See similar equations:

| 5-8p=-3p | | -280=5(-2-6x) | | 8(3x-2y)+4(-3x)+4y= | | 3+a=16 | | -16-a=1+3(a+1) | | 1x+16=36 | | 9m+4n+8m= | | 2=7(1)+b | | 4(1-x)=-20 | | 8(x+1)+7(x+1)=6x-6 | | (3x+3)(4x+5)=0 | | 50+0.05m=62.50 | | 6y-(2y-5)= | | -x+16=-7 | | -6(x-6)=72 | | 8+x+4x=13 | | a-1=4a-1 | | 1-2(x-6)=9 | | 35+x=83 | | -.5x=-1 | | -y-12=y-16 | | -22=5(x+3)-2 | | (t+10)+t+(t+20)=360 | | -49-6x=-10x+15 | | 5x+1-2=22 | | (t+10)+t+(t+20)=180 | | 6+5y=4 | | 5(4x-6)-2=42 | | 10b-25-3b=4b-2 | | -9(5-4v+7v)= | | 18-6a+4a=-4(a+3) | | -3(2x+4)=33 |

Equations solver categories